Role of HR and in Bridging the ‘Skill Gap’ in Technology Start Ups - S Kazi, Nikhat; Afzalur Rahman, Dr. (International Journal of Engineering and Technology, 2018)
You don’t Build Business , You Build People  ,and the People Build the Business-Zig Ziglar
Keywords: Human Resource Management; Start-up; Skill Gap; Technology